Ebola virus disease: are you up to date?. (2nd December 2019) - Beese, Daniel; Beckett, Gail
Abstract : While the risk of seeing cases of Ebola in general practice in the UK remains low, Daniel Beese and Gail Beckett explain the importance of keeping up to date with what to do in light of the recent disease outbreak in the Democratic Republic of Congo In July 2019, an outbreak of Ebola in the Democratic Republic of Congo was declared a Public Health Emergency of International Concern by the World Health Organization. During the last major outbreak, only a few patients with Ebola were cared for by the NHS, but media interest was high and public anxiety widespread. The fear of infection saw much time and effort put into developing a plethora of guidance, policies and protocols to prevent and control any potential risk of spread. As it is now 4 years since the last outbreak, it is an opportune time to review response arrangements.